Eksplorasi Marka SSR Terpaut Sifat Toleransi Padi Gogo terhadap Alumunium - Anggraheni, Yuliana Galih Dyan; Mulyaningsih, Enung Sri (JURNAL BIOLOGI INDONESIA, 2017)
ABSTRACTThe objective of this research was to study molecular markers were linked to upland rice tolerance of Situ Patenggang x B11930F-TB2 against Al using SSR method. The plant materials were 36 lines of Situ Patenggang x B11930F-TB2 with categories tolerant, moderate, and susceptible to acid soil based on selection in East Lampung. IR6008032 line and ITA variety used as comparative control of tolerant and susceptible. The results showed that 40 primer pairs were applied to 36 lines and allegedly 3 primer pairs that are: RM205, RM257 and RM247 linked to Al tolerance. The markers location analysis on rice chromosome listed as follows: RM205 and RM257 were located on chromosome 9 and RM247 located on chromosome 12 with genetic distance 93,12 cM, 772.62 cM and 13,05 cM, respectively.Keywords: SSR marker, upland rice, aluminium tolerance, ultisols